Dynamics between power consumption and economic growth at aggregated and disaggregated (sectoral) level using the frequency domain causality - Ashutosh Dash; Sangram Keshari Jena; Aviral Kumar Tiwari; Shawkat Hammoudeh (Journal of Risk and Financial Management, 2022)
We investigated the Granger causal relationship between the consumption of power both at the aggregate and sectoral level and economic growth in India using the frequency domain approach, which would help policy makers seek the efficient allocation of electricity via proper policy initiatives at different frequencies. We find that at the aggregate level, unidirectional causality runs from the total power consumption to economic growth, starting from the second up to the seventh quarter. In the sectoral context, the results are different. Since there is no causality between industrial power consumption and economic growth; therefore, an energy conservation policy can thus be implemented for the industrial sector. Moreover, since a bidirectional causality exists after 15 quarters for the commercial sector, a short-term policy but not an energy conservation policy could also be initiated for this sector. In the industrial and agricultural sectors, a promotional policy should be initiated because a unidirectional causality exists from sectoral power consumption to economic growth. Therefore, different and sector-specific policies would be more appropriate than a single policy for all power sectors in India in order to orient the efficient utilisation of power towards better economic development.
Keywords: 650; economic growth; frequency domain causality; power consumption; seasonal unit roots